PROLAPSUS UTERI PASCA MELAHIRKAN PADA KUCING MIX - Desty Apritya; Ratna Widyawati (VITEK : Bidang Kedokteran Hewan, 2019)
2-year-old female cat with a history of giving birth. Physical examination showed that the uterine mucosa has protusio or eversion through the vagina and vulva and hangs out. The protruding uterus was amputated and ovariohysterectomy was performed. Laparotomy was performed to ligated the ovarian artery, uterine artery, ovarian removal and vaginopexy. Antibiotic, analgesic and immunostimulants was given postoperative. The incision of the wound was closed for approximately 1 week.